Corporate governance disclosure and annual reports quality: An investigation in Vietnam context - Tran Manh Dung; Ha Hong Hanh (Cogent Economics & Finance, 2023)
Corporate governance reports (CGR) and annual reports are two fundamental corporate documents disseminated to shareholders about the companies' financial condition and operation. While the annual reports could be seen as outside appearance, the CGR reflects internal processes that an entity monitors the actions, policies, practices and decisions (Muttanachai and Thanyaorn, 2022; Ho and Taylor, 2014). Vietnam's publicly traded companies are compulsory required to provide annual reports and CGR to shareholders. The purpose of this research is to investigate the link between the level of corporate governance disclosure (CGD) and the quality of annual reports in the context of Vietnam-an emerging and dynamic country in South East Asia. The existing literature review is developed by using a bibliometric analysis (via VOSviewer software) with Scopus database from 2002 to 2022 provides comprehensive evidence for mixed effects of the level of CGD on quality of annual reports, therefore, the paper attempts to contribute to the ongoing debate by examining whether the association between CGD and the quality of annual reports is nonlinear. Furthermore, the quality of annual reports and level of CGD are measured basing on scorecard of Vietnam Listed Company Awards (VLCA) reflect the typical research issues in the context of Vietnam. A panel smooth transition regression (PSTR) model is applied in order to test the relationship and calculate the value transition threshold of 356 Vietnamese listed companies from 2017 to 2022. Empirical findings indicate that there has been a nonlinear relationship between two tested variables. In addition, the quality of annual reports positively increases when the level of CGD exceeds the value transition threshold. Hence, the listed companies with high level of CGD (exceeds threshold value) have an incentive of preparing high quality annual reports.
Keywords: 330; annual reports quality; bibliomatric analysis; level of corporate governance disclosure; listed companies; Vietnam context